A Tiered Genetic Screening Strategy for the Molecular Diagnosis of Intellectual Disability in Chinese Patients - Dai, Limeng; Zhang, Danyan; Wu, Zhifeng; Guan, Xingying; Ma, Mingfu; Li, Lianbing; Zhang, Yuping; Bai, Yun; Guo, Hong (Frontiers in Genetics, 2021)
Objective: Intellectual disability (ID) is one of the most common developmental disabilities. To identify the genetic etiology of IDs in Chongqing, we conducted a multistage study in Chinese Han patients. Methods: We collected the clinical and etiological data of 1665 ID patients, including 1604 from the disabled children evaluation center and 61 from the pediatric rehabilitation unit. Routine genetic screening results were obtained, including karyotype and candidate gene analysis. Then 105 idiopathic cases with syndromic and severe ID/DD were selected and tested by chromosomal microarray (CMA) and whole exome sequencing (WES) sequentially. The pathogenicity of the CNVs and SNVs were evaluated according to ACMG guidelines. Results: Molecular diagnosis was made by routine genetic screening in 216 patients, including 196 chromosomal syndromes. Among the 105 idiopathic patients, 49 patients with pathogenic/likely pathogenic CNVs and 21 patients with VUS were identified by CMA. 26 pathogenic CNVs underlying well-known syndromic cases, such as Williams-Beuren syndrome, were confirmed by multiplex ligation-dependent probe amplification (MLPA). Nine novel mutations were identified by WES in 35 CNV-negative ID cases. Conclusions: The study illustrated the genetic aberrations distribution of a large ID cohort in Chongqing. Compared with conventional or single methods, a tiered high-throughput diagnostic strategy was developed to greatly improve the diagnostic yields and extend the variation spectrum for the idiopathic syndromic ID cases.